Perkembangan dan Globalisasi Video Game Jepang - Arsi Widiandari (KIRYOKU, 2019)
(Title: Development and globalization Japanese Video Game ) Today, many Japanese cultural product are developing and become popular in the community, for example Japanese music, movie, anime and video game. Japanese creative industry has a big potential in economy sector and can not be underestimated. One of Japanese culture product that become popular is Japanese video game it self. Video game are considered as the pioneers of the modern game industry. This paper will discuss the development and dissemination of Japanese video game with the viewpoint of globalization.